A Systematic Literature Review: The Use of ELSA Speak on EFL Students’ Speaking Skill - Ahmad Awwabi Ribhan; Hadriana; Maria Safriyanti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
The role of speaking skill as one of the basic skills of mastering English is important to be given special attention, especially for EFL Students. The popularity of ELSA Speak as an application that is widely used to help improve speaking skills has led to a lot of research on the application. Therefore, it is necessary to conduct research with the systematic literature review method to find strong evidence about the impacts of using ELSA Speak for ELF students’ speaking skill. The systematic literature review method process consists of defining the research question, implementing a search strategy, collecting data, reporting results with PRISMA flow diagram, assessing quality, and analyzing the results by narrative synthesis. As a result, the study found 7 studies that were in accordance with the eligibility criteria to be analyzed in depth. All studies show an increase in the use of ELSA Speak from various levels of education of EFL students (Junior High School, Senior High School, and University). This application has been proven to be effective in improving pronunciation, fluency in speaking, grammatical structure, vocabulary mastery, and students' confidence in conveying ideas orally in English.